Effect of noise stress on count, progressive and non-progressive sperm motility, body and genital organ weights of adult male rats - Maryam Jalali; Ghasem Saki; Ali Reza Sarkaki; Khodabakhsh Karami; Sima Nasri (Wolters Kluwer Medknow Publications, 2012)
Aims: It was decided to investigate the effect of noise pollution on the body weight, genital organ weights, and also on sperm parameters. Setting and Design: It is a prospective study designed in vitro. Materials and Methods: A total 20 adult male wistar rats were used in this study. All rats were divided into 2 equal groups (n = 10): (1) control group and (2) experimental group. Animals of the experimental group were exposed to noise for 50 days with an intensity of 90-120 db and frequency of 300 - 350 Hz for 12 hours daily. After 50 days, at first, body weights of all animals were recorded, and then they were killed. The right epididymides were removed and also, sperm concentration and motility were determined. Each organ was weighed separately on an electronic balance. Statistical Analysis Used: Data are reported as mean ± SD and percentage. The statistical significance of difference between the control and experimental groups was determined by the unpaired t-test. Results: The weights of the testes, epididymes, seminal vesicle, ventral prostate were found to be significantly decreased in rats exposed to noise pollution when compared with the weights of the same organs obtained from control group (P < 0.05). There was a statistical difference of P < 0.05 between the 2 groups in terms of sperm concentration. Conclusions: It is concluded that noise pollution has the bad effects on sperm concentration and motility; therefore, it is supposed that homes and places of working must be build far away of noisy of factories and other places with noise.